التمظهرات المكانية في النص المسرحي الروسي المعاصر - الخزاعي، نور سعيد جبار; الغزالي، أمل حسن إبراهيم (جامعة بابل, 2019)
درس الباحثان التمظهرات المكانية في النص المسرحي الروسي المعاصر، وبرزت أهمية البحث في إلقاء الضوء على المنجزات المسرحية لأهم كتاب المسرح الروسي وتعرف مفهوم المكان وتمظهراته وتضاداته في النص المسرحي الروسي، وقد هدف البحث تعرف تمظهرات المكان في النص المسرحي الروسي، درس البحث مفهوم المكان وتمظهراته في المبحث الأول، أما المبحث الثاني تطور المسرح الروسي المعاصر، تألف مجتمع البحث من (25) نصا مسرحيا روسيا تحدد المدة الزمنية (1969–1990م)، واستخدم الباحثان المنهج الوصفي بأسلوب التحليل وتوصلا فيه إلى نتائج عديدة منها تمظهر المكان الأليف بالحديقة بصورة انتقالية عامة مفتوحة ترمز ظاهريا إلى الأماكن الاختيارية الخاصة يجمع بين الأخلاء والأصحاب في سويعات حميمة تجلب الحب والأمان والراحة، واستنتاجات كان أهمها أن الكاتب المسرحي الروسي جمع بين التضادات المكانية المفتوح والمغلق، الثابت والانتقالي، والخيالي والواقعي، وأوصى الباحثان عدة توصيات واقترحا دراسات وثبتتا المصادر. The researchers studied spatial restatements in the contemporary Russian dramatization, and the importance of the research in shedding light on the theatrical achievements of the most important book of the Russian Theater and know the concept of the place and its backlights and opposites in the Russian theatrical text, and the aim of the research has known the location of the place in the Russian theatrical text, studied The research concept of the place and its effects in the first discourse, the second part the development of the contemporary Russian theater, consisted of the Search Society of (25) Russian theatrical text determined by the time period (1969-1990), and the researchers used the descriptive method in the analysis style and reached the results of many of them the location of the pet In the park with an open public transition, ostensibly symbolizing the optional private spaces that combine eviction with the owners in intimate hours that bring love, safety, comfort, and conclusions, the most important of which is that the Russian playwright combines open and enclosed spatial opposites, constant and transitory, Imaginary and realistic, the researchers also recommended several recommendations and suggested studies and proven sources.
Keywords: المسرحيات الروسية -- الظاهرة المكانية -- الأدب المعاصر -- النقد الأدبي